Perbandingan Sistem Kesejahteraan PNS Purna Tugas di Indonesia dan Malaysia - MuttaqinÂ , Muhammad Afif (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2012)
In addition to salaries and allowances to civil servants who are still actively working, government provides pension and superannuation. The latter program aims to create prosperity after the PNS is not actively working. However, the welfare of which will be felt to be nurtured and built himself during the civil works. Why is that? This is because the governments as an employer only facilitate the program. Under the auspices of PT. Taspen, funds collected through pension and managed superannuation. Compared to retirement income, the income of civil servants when they were still actively working is higher. With that kind of policy, if a civil servant were not saving from their income, she/ he should get ready to live with lower income when they retired. Even if the pattern of the life of a retired civil servant who has been witli before retirement, one can imagine each month will be a big burden.